ANALISIS SISI PERMINTAAN DALAM PERTUMBUHAN EKONOMI DI PULAU JAWA - Rahmi (2022)
In order to achieve strong economic growth, investment is needed. Apart from investment, government spending, exports and imports play a role in influencing economic growth. This research is a quantitative research that is useful for looking at the effect of domestic investment, government spending, exports, and imports on economic growth in all provinces in Java Island. The sample used used a saturated sampling technique in six provinces on Java Island from 2012 to 2021, with a total sample of 60 samples. The data used comes from the Central Bureau of Statistics, the Investment Coordinating Board, and the Ministry of Trade. This study uses a panel data analysis test using Eviews 10. The results show that simultaneously or simultaneously domestic investment, government spending, exports and imports have an influence on economic growth. Meanwhile, partially, domestic investment and government spending have a positive effect on economic growth, exports have no effect on economic growth, and imports have a negative effect on economic growth.